Socialization factors gender-role behavior forming at girls - S. Pospelova (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The problem of girl’s gender socialization with different typological variations gender role personality structure is considered in the article. The study involved 145 girls 19-22 years old, of which three groups were formed based on the sex-role sphere structural model determination. The study has been shown mechanisms occurred gender-role behavior socialization of girls with androgynous, continuum-adjunctive and continuum- alternative sex-role models, and marked images the main problems in personalities’ gender development in modern situation.